(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
A fistula of the tenosynovium of tibialis anterior tendon and the skin in front of lower leg with discharge as a sequela of injury has not been previously reported in literature. We described two patients of cutaneous tenosynovial fistula of tibialis anterior tendon between 1994 and 2008. Both the patients were male with a mean age of 49 years. The cause of fistula was tight plater cast in one patient while the other had skin puncture by wooden stick of bushes in the jungle. Both patients presented with spontaneous drainage of clear viscous synovial fluid. Conservative treatment by immobilization and prophylactic antibiotics and surgical treatment by primary closure proved unsuccessful. In both patient’s excision of necrotic tissue and coverage with a flap resolved the drainage and healing of wound. No complication of flap noted. No recurrence was reported.